Corporate social responsibility in agricultural sector companies listed on the indonesian stock exchange - Desak Ayu Sriary Bhegawati; Yenny Verawati (Enrichment : Journal of Management, 2023)
The aim of this study was to examine the relationship between corporate social responsibility and board size, profitability, liquidity, firm age, and company size. The dependent variable, corporate social responsibility, and the independent factors in this study include board size, profitability), liquidity, company age, business size, and company size.The impact of board size, profitability, liquidity, firm age, and business size on corporate social responsibility is examined using multiple linear regression analysis in this study. Purposive sampling was employed to determine the sample size in this investigation, with a total sample size of up to 51 samples. the Indonesia Stock Exchange's official website, www.idx.co.id, corporate websites, publications, theses, and related materials are all sources of secondary data used in this study. According to the study's findings, corporate social responsibility is positively impacted by the size of the board of commissioners, profitability, and business age. Corporate social responsibility is unaffected by liquidity or company age. These findings suggest that laws and regulations to raise the number of the board of commissioners, profitability, liquidity, firm age, and company size are necessary to maximize corporate social responsibility.